Needle Fracture during Endoscopic Ultrasound-Guided Fine-Needle Aspiration of Suspicious Thoracic Lymph Nodes - Bartosz Adamowicz; Thibaut Manière; Vincent Déry; Étienne Désilets (Case Reports in Medicine)
Endoscopic ultrasound fine-needle aspiration (EUS-FNA) is used to make a cytopathologic diagnosis of suspicious lesions located around the gastrointestinal tract. It is a safe technique with few complications. The most common complications of EUS-FNA are related to pancreatic lesions (pancreatitis, bleeding, and abdominal pain). Rare complications have been noted such as stent malfunction, air embolism, infection, neural and vascular injuries, and tumor cell seeding. There are very few studies examining equipment malfunctions. We report a case of needle fracture during the EUS-FNA of suspicious thoracic lymph nodes in a 79-year-old man investigated for unexplained weight loss.